2022
DOI: 10.3390/jpm12111783
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cardiac Stereotactic Radiation Therapy (SBRT) to Manage Ventricular Tachycardia: A Case Report, Review of the Literature and Technical Notes

Abstract: Background: among cardiac arrhythmias, ventricular tachycardia (VT) is one that can lead to cardiac death, although significant progress has been made in its treatment, including the use of implantable cardioverter-defibrillators (ICD) and radiofrequency catheter ablation. Nevertheless, long-term recurrence rates remain in about half of patients and drastically impact the patient’s quality of life. Moreover, recurrent ICD shocks are painful and are associated with higher mortality and worsening of heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…SBRT, originally developed for oncological purposes, has been adapted to target arrhythmogenic substrates within the heart [58]. The precision of SBRT allows for the focused delivery of high-dose radiation targeted to a specific area of tissue [59], potentially abolishing the arrhythmogenic focus without the need for invasive catheterization. Early clinical trials have shown promising results in reducing the burden of refractory VT, particularly in patients where conventional catheter ablation techniques have previously failed [60].…”
Section: Radiotherapymentioning
confidence: 99%
“…SBRT, originally developed for oncological purposes, has been adapted to target arrhythmogenic substrates within the heart [58]. The precision of SBRT allows for the focused delivery of high-dose radiation targeted to a specific area of tissue [59], potentially abolishing the arrhythmogenic focus without the need for invasive catheterization. Early clinical trials have shown promising results in reducing the burden of refractory VT, particularly in patients where conventional catheter ablation techniques have previously failed [60].…”
Section: Radiotherapymentioning
confidence: 99%